2011
DOI: 10.1007/978-94-007-0415-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Neanderthals and Monkeys in the Würmian of Central Europe: The Middle Paleolithic Site of Hunas, Southern Germany

Abstract: The site of Hunas is a cave ruin, filled with bedded sediments up to the roof. About 20 m sediments from the top down were excavated and yielded Middle Paleolithic artifacts as well as numerous faunal remains, including Macaca. With a single human molar, the site is one of the rare Neanderthalian localities in Germany. New TIMS-U/Th dating of speleothems at the base of the profile indicate that the whole sequence was not deposited during the late Middle Pleistocene as previously thought, but during the last gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…These signals are more likely to be the result of animal denning and excrement accumulations (Braillard et ACCEPTED MANUSCRIPT , 2004), however climatic input cannot be excluded (Holliday and Garther, 2006) especially when the enhancement of the magnetic signal is taken into consideration (Jordanova, 2016). A similar result was obtained at Hunas cave (Rosendahl et al, 2011), where layer J consisting of yellowish grey silty material containing medium fine scree also had increased values of magnetic signal and was also dated to GIS (Greenland Interstadial)…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These signals are more likely to be the result of animal denning and excrement accumulations (Braillard et ACCEPTED MANUSCRIPT , 2004), however climatic input cannot be excluded (Holliday and Garther, 2006) especially when the enhancement of the magnetic signal is taken into consideration (Jordanova, 2016). A similar result was obtained at Hunas cave (Rosendahl et al, 2011), where layer J consisting of yellowish grey silty material containing medium fine scree also had increased values of magnetic signal and was also dated to GIS (Greenland Interstadial)…”
Section: Resultssupporting
confidence: 76%
“…A C C E P T E D M A N U S C R I P T 8 (Bocksteinhöhle, Bockstein-Törle, Hohlenstein-Stadel, Hohlenstein-Bärenhöhle and Vogelherd) (Bolus, 2003) and in Bavaria (Hunas) (Rosendahl et al, 2011). The problem is that few of them have produced substantial data for detailed environmental interpretation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the presence of primate elements is so low at these sites that the baboons were conceivably consumed by predators such as leopards and not by humans (Badenhorst 2022). Moving into western Europe, Rosendahl et al (2011) recorded that Neanderthals and macaques co-occurred at the Würmian site of Hunas (Germany). Furthermore, using a modeling approach, Elton & O'Regan (2014) human predation on macaques was one of the factors influencing the extinction of these primates on the European continent during the Late Pleistocene.…”
Section: Ancient Primates and Past Humans Before The Rise Of The Anth...mentioning
confidence: 99%
“…However, they must have co-existed alongside earlier Homo species for over 1 million years (Oms et al, 2000;Toyo-Moyano et al, 2013), with macaques and hominins found at a number of Early and Middle Pleistocene sites including Cueva Negra del Estrecho del Quípar and Solana del Zamborino in Spain, and Galeria Pesada in Portugal (see Marigó et al, in press). Evidence of hominins (both fossils of H. neanderthalensis and/or stone tools) is also present with Macaca (although not always within the same levels) at a number of Late Pleistocene sites, including Hunas (Rosendahl et al, 2011), Grotta degli Orsi Volanti (Mazza et al, 2005), Kugelsteinhöhle II (Fladerer, 1991), Cova Negra (Marigó et al, in press) and Lezetxiki (Castanos et al, 2011). Modern ecological studies indicate that Barbary macaques do not live comfortably alongside humans, and unlike baboons, vervets and some Asian macaques, do not exploit human habitats (Menard, 2002).…”
Section: Macaca Sylvanus -A Forgotten Late Pleistocene Extinction?mentioning
confidence: 99%